Literature Review on Valuation and Accounting Recognition for Heritage Assets - Iswari, Yuni; Mediawati, Elis (International Journal of Business, Law, and Education, 2024)
Historic assets can also be said to be unique assets because of the diverse ways of obtaining them ranging from development, purchase, donation, inheritance, booty, or confiscation and their management and maintenance are protected by the local government (Agustini, 2011). In accordance with applicable laws the validity of a historic asset can be proven by legality to maintain the unlimited existence of historic assets. There are several valuation models for Historic Assets based on accounting standards that apply in the world, namely: Accounting Policy Act, Generally Recognized Accounting Practice (GRAP) 103, Financial Reporting Statements (FRS) 30, and Government Accounting Standards Manual (PSAP) 07 (2010). These differences arise due to the conditions and situations in each country in adopting a guideline that regulates accounting for heritage assets as well as the characteristics of heritage assets that are considered unique and diverse (Ouda, 2014). The accounting treatment for historic assets varies greatly depending on the nature of the asset and also the nature of the entity that holds it. Based on the results of the literature review conducted by the author, regarding how accounting records for heritage assets in Indonesia provide diverse results where there are heritage assets that are recorded in accordance with applicable standards and there are also heritage assets that are not in accordance with applicable accounting standards, namely PSAP 07 2010 regarding Fixed Asset Accounting. This is due to the inadequate quality of human resources who understand the assessment and accounting treatment of heritage assets and unclear policies in the treatment of heritage assets.